Differences in Esthetic Line (e-line) of class III skeletal malocclusion before and after orthognathic surgery treatment using ricketts cephalometric analysis: Study descriptive - Hadi, Azmil; Mardiati, Endah; Evangelina, Ida Ayu; Laviana, Avi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Class III skeletal malocclusion is a complex dentoskeletal disorder and is the most difficult malocclusion to treat, especially in patients who have completed their pubertal growth period. In severe cases, orthodontic treatment and orthognathic surgery are required. There are various methods to evaluate the results of orthognathic surgery, one of which is the Ricketts Esthetic Line (E-line) analysis that can be used to view soft tissue changes before and after orthognathic surgery. The aim of the study was to analyze changes in the soft tissue profile of the lips using Ricketts Esthetic line (E-line) analysis in class III skeletal malocclusion after orthognathic surgery for both one-jaw surgery and two-jaw surgery. Methods: This research is descriptive comparative analysis. The study samples were lateral cephalograms before and after orthognathic surgery with one or two jaw surgery techniques. The study subjects were 8 patients with skeletal class III malocclusion who underwent orthognathic surgery at the Oral Surgery Department of the Padjadjaran University Hospital in Bandung. Cephalometric analysis was tested by paired t-test to see differences in lip soft tissue before and after orthognathic surgery based on Ricketts E-line analysis. Results: There were significant differences in the results of analysis of the soft tissue of the upper and lower lips on the Esthetic line (E-Line) before and after orthognathic surgery. orthognathic was also significantly different p < 0.0204. The results of the comparison test between before after orthognathic surgery compared to standard normal Ricketts E-line analysis showed that the e-line at the distance of the upper lip was significantly different p<0.0072, while for the lower lip it was not significantly different p>0.2413. Conclusion: Orthodontic treatment with orthognathic surgery in class III skeletal malocclusion can significantly change the Ricketts E-line method, except that the distance of the lower lip to the Ricketts e-line norm is not significantly differentKEY WORDS: skeletal class III malocclusion, orthognatic surgery, Ricketts esthetic line (E-line) analysis.Perbedaan esthetic line (e-line) maloklusi skeletal kelas III sebelum dan setelah perawatan bedah ortognati menggunakan analisis sefalometri rickettsABSTRAKPendahuluan: Maloklusi skeletal kelas III merupakan kelainan dentoskeletal yang kompleks dan merupakan suatu maloklusi yang perawatannya paling sulit terutama pada pasien yang sudah selesai masa pertumbuhan pubertalnya, dimana pada kasus yang parah diperlukan perawatan ortodonti dan bedah ortognati. Terdapat berbagai metode untuk mengevaluasi hasil perawatan bedah ortognati, salah satunya adalah analisis Ricketts Esthetic Line (E-line) yang dapat digunakan untuk melihat perubahan jaringan lunak sebelum dan setelah perawatan bedah ortognati. Tujuan penelitian menganalisis perubahan profil jaringan lunak bibir  menggunakan analisis Ricketts Esthetic line (E-line) pada maloklusi skeletal kelas III setelah perawatan  bedah ortognati baik pada pembedahan satu rahang dan pembedahan dua rahang. Metode: Jenis penelitian deskriptif analitis komparatif. Sampel penelitian berupa sefalogram lateral sebelum dan setelah perawatan bedah ortognati dengan teknik pembedahan satu ataupun dua rahang Subjek penelitian 8 pasien dengan maloklusi skeletal kelas III yang menjalani bedah ortognati di bagian Bedah Mulut RSGM UNPAD Bandung. Analisis sefalometri diuji dengan uji- t berpasangan untuk melihat perbedaan jaringan lunak bibir sebelum dan setelah bedah ortognati berdasarkan analisis E-line Ricketts. Hasil: Terdapat perbedaan yang signifikan hasil analisis jaringan lunak bibir atas dan bawah terhadap Esthetic line (E-Line) sebelum dan setelah bedah ortognati jarak bibir atas sebelum dan setelah bedah ortognati berbeda secara bermakna p<0,0148, untuk jarak bibir bawah sebelum dan setelah edah ortognati juga berbeda secara bermakna p<0,0204. Hasil uji perbandingan antara sebelum  setelah bedah ortognati dibandingkan dengan standar normal analisis E-line Ricketts maka e-line pada  jarak bibir atas berbeda secara bermakna  p<0,0072, sedangkan untuk bibir bawah tidak  berbeda secara bermakna p>0,2413. Simpulan: Perawatan ortodonti dengan bedah ortognati pada maloklusi skeletal kelas III dapat mengubah E-line metode Ricketts secara signifikan, kecuali jarak bibir bawah terhadap norma e-line Ricketts yang tidak  berbeda secara bermaknaKATA KUNCI: maloklusi skeletal kelas III, bedah ortognati, analisis Ricketts Esthetic Line (E-line).